KRITIK SOSIAL PADA LIRIK LAGU KARYA IWAN FALS: KAJIAN STILISTIKA - Faizah, Inayah Isnaini; Ekawati, Mursia; Pradita, Linda Eka (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2024)
Song lyrics are a form of literary work that originally from the outpouring of personal feelings, emotions, expressions and experiences from the author. Through a song, we can find the language style used by each writer. This research method is descriptive qualitative. This research uses a note-reading technique with all the lyrics of the song and then records all the analysis results. The data source in this research is the lyrics of the songs